Pemodelan Sortasi Buah Cabai Berdasarkan Karakteristik Morfologi Melalui Pendekatan Analisis Citra Digital - Arifah Husna; Fatiyah Rahmah; Honesh Setia N.; Latifah Dwi S.; Yussy Purwaningsih (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Sorting is an important stage in postharvest handling of chili peppers to obtain products with uniform quality. Manual sorting processes generally require more time and have the potential to produce errors due to observer subjectivity. This study aimed to model chili pepper (Capsicum sp.) sorting using a digital image analysis approach with ImageJ software and to compare its measurement effectiveness with conventional manual methods. The study employed an experimental method with a quantitative approach through several stages, including manual measurement, image acquisition, image processing using ImageJ, and data analysis. The observed parameters included fruit size, object area, color intensity, and visual characteristics of chili peppers. The results showed that measurements obtained using ImageJ exhibited a similar trend to manual measurements in identifying the relative size of chili fruits. The object area values generated through image analysis indicated variations in size among samples, while color characteristics reflected differences in fruit maturity levels. The use of ImageJ provided a more objective, faster, and more consistent measurement process compared to manual methods. Digital image analysis has potential for further development as an automated sorting system in chili postharvest handling.